Suicide Risk and Prevention During the COVID-19 Pandemic: One Year On. Issue 4 (2nd October 2022) - Sinyor, Mark; Knipe, Duleeka; Borges, Guilherme; Ueda, Michiko; Pirkis, Jane; Phillips, Michael R.; Gunnell, David
Abstract: Emerging data from high and upper-middle-income countries indicate that suicide rates generally did not increase during the initial months of the COVID-19 pandemic, yet the pandemic's impact on suicide is complex. We discuss the nuances of this relationship, how it may evolve over time, and describe the specific steps that governments and societies must take to mitigate harm and prevent suicides in the late stages and aftermath of the pandemic.